(untitled) (Revista Educação Especial em Debate, 2018)
Denise Meyrelles de Jesus (UFES) Edson Pantaleão Alves (UFES) Hiran Pinel (UFES) Ivone Martins de Oliveira (UFES) Lucyenne Matos da Costa Vieira Machado (UFES) Reginaldo Célio sobrinho (UFES) Rogério Drago (UFES) Sonia Lopes Victor (UFES)